Outcomes following less-invasive-surfactant-administration in the delivery-room. (April 2022) - Arattu Thodika, Fahad M.S.; Ambulkar, Hemant; Williams, Emma; Bhat, Ravindra; Dassios, Theodore; Greenough, Anne
Abstract: Background: Less invasive surfactant administration (LISA) on the neonatal unit reduces the need for mechanical ventilation and bronchopulmonary dysplasia (BPD). Aims: To assess the immediate and longer-term efficacy of LISA to prematurely born infants in the delivery-room. Study design: A case control study with inborn historical controls matched for gestational age, birthweight and gender to each LISA infant. Subjects: Infants born between 26 +0 weeks and 34 +6 weeks of gestational age. Outcome measures: Respiratory function monitoring before and after LISA and need for mechanical ventilation within 72 h of birth. Results: Ninety-nine infants, median gestational age of 32 +4 (range:27 +0 –34 +6 ) weeks, were prospectively recruited. The respiratory rate and inspired oxygen (FiO2 ) decreased two minutes after LISA and there was a reduction in the FiO2 requirement at two hours post birth. Compared to historical controls, LISA administration was associated with a reduction in the need for mechanical ventilation within 72 h after birth (20.2% versus 56.6% p < 0.001) the incidence of moderate to severe BPD (8.2% versus 20.2%, p = 0.02) and the median costs of neonatal intensive care stay (£1218 versus £2436, p = 0.03) and total neonatal unit stay (£12, 888 versus £17, 240, p = 0.04). A high FiO2 in the delivery-room pre-LISA (median 0.75 versus 0.60, p = 0.02) was associated with LISA failure, that is mechanical ventilation within 72 h of birth. Conclusions: LISA to prematurely born infants in the delivery-room was associated with reductions in the need for mechanical ventilation and costs of care, but was less successful in those with initial, more severe respiratory disease. Highlights: LISA was feasible in the delivery-room for infants born 26 +0 weeks to 34 +6 weeks. There were improvements in respiratory outcomes post LISA. LISA reduced the need for mechanical ventilation, BPD and healthcare costs. An initial high FiO2 requirement was associated with LISA failure.